2001
DOI: 10.1177/1077559501006002003
|View full text |Cite
|
Sign up to set email alerts
|

Views of Child Sexual Abuse in Two Cultural Communities: An Exploratory Study among African Americans and Latinos

Abstract: This exploratory study investigates knowledge and ideas about child sexual abuse among African Americans and Latinos through focus group discussions. Participants defined and described child sexual abuse, acknowledged that it occurred in their communities, and expressed their sense that family risk factors, risky institutions, and offender propensities were its root causes. Latino participants identified cultural transitions as another contributor. Responses and conversational style differed somewhat by gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 23 publications
2
60
0
2
Order By: Relevance
“…With regard to cultural concerns related to oppression and views that discourage assertive behaviour, it is true that many cultures, including Asian, Puerto Rican, other Latino cultures, AfricanAmerican, Native-American and others (Fontes, 1993;Fontes et al, 2001;Wood and Mallinckrodt, 1990) may perceive assertive behaviour, particularly by women and children, as disrespectful, and may refrain from utilising assertive behaviour for fear of being perceived negatively due to issues of discrimination and oppression. Compounded by these culturally relevant factors, many children and families may be hesitant to report CSA to the systems they distrust due to the discriminatory and oppressive practices directed towards them by these very systems (Fontes, 1993).…”
Section: Programme Satisfactionmentioning
confidence: 96%
See 2 more Smart Citations
“…With regard to cultural concerns related to oppression and views that discourage assertive behaviour, it is true that many cultures, including Asian, Puerto Rican, other Latino cultures, AfricanAmerican, Native-American and others (Fontes, 1993;Fontes et al, 2001;Wood and Mallinckrodt, 1990) may perceive assertive behaviour, particularly by women and children, as disrespectful, and may refrain from utilising assertive behaviour for fear of being perceived negatively due to issues of discrimination and oppression. Compounded by these culturally relevant factors, many children and families may be hesitant to report CSA to the systems they distrust due to the discriminatory and oppressive practices directed towards them by these very systems (Fontes, 1993).…”
Section: Programme Satisfactionmentioning
confidence: 96%
“…Compounded by these culturally relevant factors, many children and families may be hesitant to report CSA to the systems they distrust due to the discriminatory and oppressive practices directed towards them by these very systems (Fontes, 1993). While not directly addressed in the literature on sexual abuse education, researchers have suggested that the cultural beliefs, issues of oppression and the context of specific situations be taken into consideration when conducting assertiveness training (Wood and Mallinckrodt, 1990) and sexual abuse prevention programmes (Fontes et al, 2001) with minority populations. Promising results have been found with research that has been conducted with 'Only a few studies reported negative side-effects in a small number of participants' 'Cultural beliefs, issues of oppression and the context of specific situations' children from diverse cultural and ethnic backgrounds who were sexually abused.…”
Section: Programme Satisfactionmentioning
confidence: 97%
See 1 more Smart Citation
“…A more recent case reported sexual harassment toward the daughter by her father 11 . Although most reported cases describe female victims, and mostly from western countries, sexual abuse during childhood is reported by both genders and among almost all ethnic groups and also different cultures 3,4,6,7,[12][13][14][15][16][17] . In a recent study by Saewyc et al 17 ethnic variation was minor, with African American, Native American, and Hispanic teens being slightly more likely to report abuse than White or Asian American youth 17 .…”
Section: Introductionmentioning
confidence: 98%
“…En base al análisis de las publicaciones nacionales e internacionales al respecto, se estudiará la existencia de posibles diferencias en las respuestas de los estudiantes en función del sexo (Davis y Lee, 1996;Davies y Rogers, 2009;Graham et al, 2007;RomeroSánchez y Megías, 2009;Spencer y Tan, 1999), el nivel educativo (Xenos y Smith, 2001) y el país de origen del encuestado (Fontes, Cruz y Tabachnick, 2001;Hestick y Perrino, 2009;Rodríguez-Srednicki y Twaite, 1999). Se hipotetiza que, pese a utilizar un instrumento y muestra diferentes, los estudiantes presentarán algunos conocimientos sobre abuso sexual infantil pero mantendrán creencias erróneas y estereotipos al respecto, de forma similar a lo obtenido en el estudio de López (1994) con población general.…”
Section: Introductionunclassified